The circulation of people. A critical discussion on the impact of glacier shrinkage upon population mobility in the bolivian andes - Kaenzig, Raoul (Neuchatel MAPS - Maison d'Analyse des Processus Sociaux Institut de Géographie, 2013)
This article examines the role of glacial retreat on people migration in the Bolivian Andes. In the Andean region, glacial retreat is one of the most noticeable effects of global warming. Significant acceleration in glacial melting has been observed since the 1980s and glacial runoff is vital to the region, supporting local ecosystems as well as providing water for drinking, irrigation and energy production. In academic literature, international medias and NGO reports it is often assumed that these impacts are severely affecting the livelihood of the local population who may be forced to migrate. Based upon a literature review and a case study in the Bolivian Andes, this paper brings a critical discussion on this assumption. The confrontation of two bodies of academic literature, the first on migration and climate change and the second on glacial retreat impacts allows the conceptualisation of some mechanisms to understand how the impact of glacial retreat may be considered as migration drivers. These mechanisms are then illustrated and discussed with a case study that brings empirical insights on mobility patterns of rural communities living on the edge of a retreating glacier.
Working Paper
Keywords: Migration; climate change; glacier; glacial retreat; Andes; mountain; Bolivia